Materials Characterisation V 2011
DOI: 10.2495/mc110191
|View full text |Cite
|
Sign up to set email alerts
|

Tension/compression test of auto-body steel sheets with the variation of the pre-strain and the strain rate

Abstract: This paper investigates the tension/compression hardening behaviour of autobody steel sheets with the variation of the pre-strain and the strain rate. To conduct tension/compression tests with the variation of the pre-strain and the strain rate, an experimental method was established by using a newly developed clamping device to suppress buckling of a specimen. The clamping device provides the supporting force from compression-type coil springs during the test with a conventional dynamic material fatigue testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“…These results were achieved with a maximum lateral force of approximately −2.3 kN (−517 psi), which is significantly less than the 8 kN (1800 psi) to 10 kN (2250 psi) restoring force reported in the literature [31,19]. These low friction results validated the principal philosophy behind our design.…”
Section: Resultssupporting
confidence: 66%
“…These results were achieved with a maximum lateral force of approximately −2.3 kN (−517 psi), which is significantly less than the 8 kN (1800 psi) to 10 kN (2250 psi) restoring force reported in the literature [31,19]. These low friction results validated the principal philosophy behind our design.…”
Section: Resultssupporting
confidence: 66%
“…Yoshida et al [39] suggested bonding five pieces of sheets together before machining them so that the thickness of the specimen was 5.0 mm. Bae and Hug [33] used a spring-loaded clamping device in various strain rates. More recently, a transparent wedge device was designed to prevent the buckling of thin sheets, allowing full field strain measurements of the specimen using digital imaging methods [40].…”
Section: Methodsmentioning
confidence: 99%
“…This test only achieves a maximum deformation of approximately 3%; however it could be appropriate to characterize low deformation processes such as the roll levelling process, in which the maximum material deformation is usually lower than 2%. Nevertheless, the test is difficult to perform, due to the tendency of the specimen to buckle in compression [33].…”
Section: Introductionmentioning
confidence: 99%
“…Using experimental method proposed by Bae and Huh, 2011, tension/compression tests of SPCC and DP780 were carried out at the strain rates of 0.001/s and 1/s. True stres the tension/compression tests and hardening curves expand with the increase strain rates for both steel sheets.…”
Section: Finite Element Modeling and Materials Propertymentioning
confidence: 99%
“…However, strain rate is known to be an important parameter to influence the hardening behavior of sheet metals. Moreover, Bae and Huh (2011) recently carried out the tension/compression test of steel sheets in order to investigate the effect of the strain rate on the tension/compression hardening behaviour. The tension/compression hardening behaviour of steel sheets changes sensitively with the variation of the strain rate.…”
Section: Introductionmentioning
confidence: 99%